Unity-Engine-Based E-Module to Increase Learning Results on Online Learning - Sudi Dul Aji; Arief Rahman Hakim; Klarisa Megaria Novita; Muhammad Nur Hudha (AL-ISHLAH: Jurnal Pendidikan, 2023)
The development of technology is currently moving very fast. These developments affect student learning in schools. However, the teachers have not used it properly, so learning is not in accordance with the needs of students. This is also due to the limited teaching materials used. This research aims to develop the teaching materials of the unity-based E-module and its utilization. The stages started from analysis, design, development, and implementation. The instruments were used to determine the feasibility of validation sheets and questionnaires. The results of the study indicate that teaching materials are feasible to use. The assessment of media experts indicates this gets a percentage score of 88%, the assessments of material experts get a percentage score of 75%, the assessments from linguists get a percentage score of 86%, and the assessments by teachers get a percentage score of 95%. Based on the explanation of the research results above, it can be concluded that the teaching materials of Unity engine-based energy E-Module and its utilization can be used in the learning process.